Pressure injury in adult patients hospitalized and served by a specialized skin service in the largest hospital in Paraná (Research, Society and Development, 2020)
Objective: to identify the characteristics of pressure injuries (LPP) of hospitalized adults assisted by a service of prevention, evaluation and treatment of skin injuries. Methodology: sectional descriptive study with documentary collection performed in the records of a specialized service, in a teaching hospital, in Curitiba, from January 21 to March 21, 2020. Results: of the 18 patients investigated, 88.9% were white, 61.1% were male, aged over 60 years (55.5%). The number of LPP developed by these patients ranged from 1 to 3, totaling 24 injuries; 37.5% (n = 9) injuries by deep tissue pressure, 25% (n = 6) stage 2, 20.8% ( n = 5) stage 1, 8.3% (n = 2) stage 3, 8.3% (n = 2) not classifiable and 8.3% (n = 2) by pressure related to devices. The sacral region was the most affected, followed by the calcaneus. Regarding clinical conditions and health habits, systemic arterial hypertension stands out as a pre-existing condition. The main risk factors were classified as: being restricted to bed, use of diapers and inadequate nutrition. Conclusion: the characteristics found in this study are similar to studies already published with this scope, with a clear need for continuity of care with the implementation of preventive measures for critical, elderly and frail patients based on the best evidence in order to reduce this adverse event.